Transposable elements (TEs) contribute to stress‐related long intergenic noncoding RNAs in plants. (April 2017) - Wang, Dong; Qu, Zhipeng; Yang, Lan; Zhang, Qingzhu; Liu, Zhi‐Hong; Do, Trung; Adelson, David L.; Wang, Zhen‐Yu; Searle, Iain; Zhu, Jian‐Kang
Summary: Noncoding RNAs have been extensively described in plant and animal transcriptomes by using high‐throughput sequencing technology. Of these noncoding RNAs, a growing number of long intergenic noncoding RNAs (lincRNAs) have been described in multicellular organisms, however the origins and functions of many lincRNAs remain to be explored. In many eukaryotic genomes, transposable elements (TEs) are widely distributed and often account for large fractions of plant and animal genomes yet the contribution of TEs to lincRNAs is largely unknown. By using strand‐specific RNA‐sequencing, we profiled the expression patterns of lincRNAs in Arabidopsis, rice and maize, and identified 47 611 and 398 TE‐associated lincRNAs (TE‐lincRNAs), respectively. TE‐lincRNAs were more often derived from retrotransposons than DNA transposons and as retrotransposon copy number in both rice and maize genomes so did TE‐lincRNAs. We validated the expression of these TE‐lincRNAs by strand‐specific RT‐PCR and also demonstrated tissue‐specific transcription and stress‐induced TE‐lincRNAs either after salt, abscisic acid (ABA) or cold treatments. For Arabidopsis TE‐lincRNA11195, mutants had reduced sensitivity to ABA as demonstrated by longer roots and higher shoot biomass when compared to wild‐type. Finally, by altering the chromatin state in the Arabidopsis chromatin remodelling mutant ddm1, unique lincRNAs including TE‐lincRNAs were generated from the preceding untranscribed regions and interestingly inherited in a wild‐type background in subsequent generations. Our findings not only demonstrate that TE‐associated lincRNAs play important roles in plant abiotic stress responses but lincRNAs and TE‐lincRNAs might act as an adaptive reservoir in eukaryotes. Significance Statement: Noncoding RNAs have been extensively described, but the origins and functions of many long intergenic noncoding RNAs (lincRNAs) remain to be explored. Here we describe hundreds of transposable element‐associated lincRNAs (TE‐lincRNAs) in rice, maize and Arabidopsis and demonstrate their tissue‐specific transcription. By perturbing chromatin structure, we show that novel TE‐lincRNAs are transcribed and inherited across generations, suggesting that lincRNAs might act as an adaptive reservoir in eukaryotes; indeed we show that loss of function of a TE‐lincRNA attenuates abiotic stress tolerance.